Technological Environment and Technology Entrepreneurship: A Cross‐Country Analysis. (21st August 2015) - Colovic, Ana; Lamotte, Olivier
Abstract : Recent years have seen growing interest in the influence of the environment on entrepreneurship. However, little is known about the impact of the country‐level technological environment on the creation of new technology‐based firms. This study investigates the relationship between the technological environment (measured by the amount of investment in R&D, and access to information and communication technology [ICT] infrastructure) and technology entrepreneurship, in 54 countries during the years 2005 to 2010. Using data from the Global Entrepreneurship Monitor, and the World Bank Development Indicators, we identify a significant, robust inverted U‐shaped relationship between R&D investment at country level and the likelihood of technology entrepreneurship. We also find evidence of a positive relationship between access to ICT infrastructure and the likelihood of technology entrepreneurship.